Synthesis of 1-Palmitoyl-2-((E)-9- and (E)-10-nitrooleoyl)-sn-glycero-3-phosphatidylcholines - Lehr, Alexander; Frank, Andrea; Münch, Winfried; Dietz, Ulrich; Nubbemeyer, Udo (Synthesis, 2019)
Extensive investigation of nitrated phospholipids in connection with various biologically important processes requires reliable access to suitable material. A selective chemical synthesis introducing a defined nitrofatty acid at the sn-2 position of a 2-lyso sn-glycero-3-phosphatidylcholine was developed. Given that the nitroalkene moiety of both reactant nitrofatty acid derivative and the product esters is characterised by particular sensitivity to nucleophile addition and, depending on the intermediate, subsequent olefin isomerisation and retro-Henry-type reaction, a reliable two-step ester formation was introduced. The activation of the nitrofatty acid succeeded after reaction with trichlorobenzoyl chloride, and the mixed anhydride could be isolated via extractive work-up. Subsequent reaction with 1-palmitoyl-2-lyso-sn-glycero-3-phosphatidylcholine enabled the sn-2 esterification to be achieved with high yield by using a minimum of reagents, avoiding the formation of side products and facilitating final isolation and purification.
Keywords: nitrooleic acid; nitro phospholipid; nitrooleoyl glycero 3-phosphatidylcholine; ester formation; mixed anhydride